Facile route to synthesising mesoporous SBA-15 using phosphoric acid. (4th March 2019) - Dan, Hui; Xian, Qiang; Chen, Li; Xiong, Tianheng; Chen, Luyu; Huang, Qihong; Jiang, Xiaoxue; Yi, Facheng; Ding, Yi
ABSTRACT: A facile route has been developed to synthesise mesoporous SBA-15 using mild H3 PO4 (replacing the most commonly used strong acid HC1) as the medium and the effects of H3 PO4 concentration and synthesis temperature on the mesostructure and morphology of the resultant materials investigated. The results demonstrate that a more ordered structure can be obtained at low H3 PO4 concentration (1–2 M), while a higher H3 PO4 concentration (3–4 M) results in a less ordered structure. Furthermore, the morphology of SBA-15 particles transforms from rod-like to sphere-like with increasing H3 PO4 concentration.